POS0564 COULD THE EXTENT OF CPP DEPOSITION PROVIDE NOVEL INSIGHTS INTO THE PATHOGENETIC MECHANISMS OF CPPD? PRELIMINARY RESULTS FROM AN ULTRASOUND STUDY - Filippou, G.; Sirotti, S.; Lucia, A.; Cirillo, D.; Fabbri, R.; Varvaro, A.; Pellegrino, G.; Cumbo, E.; Sarzi-Puttini, P. (Annals of the rheumatic diseases, 2024)
Background:Calcium pyrophosphate deposition (CPPD) is a multifaceted condition that could remain asymptomatic or evolve in various types of arthritis, ranging from acute monoarthritis to severe forms of polyarticular involvement. However, pathogenetic mechanisms and especially prognostic factors for the evolution of CPPD have not been identified yet.Objectives:This study aims to assess the relationship between the extent and the frequency of CPPD in various anatomical structures in the knees and wrists and the different CPPD phenotypes.Methods:This is a cross-sectional study conducted between 04/2023 and 12/2023. Consecutive patients diagnosed with CPPD disease according to the 2023 ACR/EULAR classification criteria, and patients with evidence of asymptomatic CPPD on US (not meeting the classification criteria) according to the OMERACT US definitions, were enrolled. The ultrasonographic assessment was carried out by 2 rheumatologists, experienced in CPPD and ultrasound, whose reliability has been previously tested. The OMERACT scoring system was used to evaluate the extent of CPPD. Descriptive statistical analyses were performed to analyze the collected data.Results:44 patients were enrolled, 63.6% (28/44) were female, with a mean age of 73.8 years (±9SD). Patients were classified into 4 clinical subsets according to the 2011 EULAR recommendations: 18 had acute CPP crystal arthritis, 15 had chronic CPP crystal arthritis, 5 had osteoarthritis (OA) with CPPD, and 6 presented asymptomatic CPP deposition. The anatomical structures most frequently affected were the medial meniscus (MM) and lateral meniscus (LM), both observed in 97.7% (43/44) of patients, followed by the triangular fibrocartilage complex (TFCC) in 93.2% (41/44). Hyaline cartilage (HC) showed the least frequent involvement, observed in 72.7% (32/44) of patients. MM exhibited the highest bilateral involvement (84.1% of cases), followed by the LM (81.8%), TFCC (77.3%), and finally HC (45.5%). No significant differences were found regarding the frequency of involvement of the various sites by subsets of disease, except for the asymptomatic subset, in which the bilateral involvement was lower in comparison to the other subsets. Regarding the extent of deposition at the patient level, the overall mean score (from 0 to 24) was 12.8 (SD ±4.9, median 13). Patients with acute CPP crystal arthritis had a mean score of 12.2 (SD ±3.9, median 12), those with chronic CPP crystal arthritis had a mean score of 13.5 (SD ±4.8, median 13), patients with OA with CPPD had the highest mean score of 17.6 (SD ±1.1, median 18), and patients with asymptomatic CPPD had the lower mean score of 8.5 (SD ±6.5, median 6). At tissue level, menisci had the highest burden of deposition (from 0 to 3), with a mean of 1.84 (SD ±0.9, median 2), followed by TFCC with a mean scoring of 1.7 (SD ±0.9, median 2), while HC exhibited the lower burden of deposition, with a mean of 1.02 (SD ±1, median 1) (Figure 1).Conclusion:Among the anatomical structures involved in CPPD disease, fibrocartilaginous structures appear to be more frequently and more severely affected, whereas HC demonstrates less frequent involvement. When analysing the extent of CPPD within the 2011 EULAR subsets, a higher crystal burden was observed in patients with the subset OA with CPPD, compared to those experiencing acute CPP flares or chronic arthritis. Asymptomatic patients display the lowest crystal burden. The observed differences in CPPD extent among various phenotypes can be interpreted in several ways. Firstly, a higher crystal burden could be indicative of an increased risk of developing symptomatic disease, as evidenced by the lower crystal extent observed in asymptomatic CPPD. Further, the presence of OA could appear to promote crystal deposition, or conversely, the presence of CPPD could contribute to the development of OA, as the subset OA with CPPD had the highest extent of deposition. Alternatively, the shedding of crystals could promote inflammation leading to a lower extent of deposition in inflammatory diseases. A lot has still to be done to shed some light on this complex condition.Figure 1.Overall distribution of the scores in CPPD patients.Acknowledgements:NIL.Disclosure of Interests:None declared.